Composite proteomic and metabolomic plasma biomarkers for detection of colorectal, lung and ovarian cancers - Åkerrén Ögren, Jim; Ekström, Joakim; Rameika, Natallia; Torell, Emma; Larsson, Chatarina; Stoimenov, Ivaylo; Micke, Patrick; Gyllensten, Ulf; Hellström, Mats; Glimelius, Bengt; Stålberg, Karin; Sjöblom, Tobias (Uppsala University, 2025)
The dataset includes measurements of the levels of 165 plasma proteins and 244 metabolites in 937 individuals with malignant, pre-malignant or non-malignant condition, sampled by the Uppsala-Umeå cancer biobank (U-CAN). The sampled population consists of 330 individuals with colorectal cancer, 304 individuals with lung cancer, 184 individuals with ovarian cancer and 119 non-cancer controls. The data for the protein levels in the plasma were acquired by a suspension array ELISA system (BioPlex 200, Bio-Rad) with 10 antibody panels in house at Uppsala University, while the plasma levels of the metabolites were acquired by Nuclear Magnetic Resonance (NMR) spectroscopy, carried out at the blood analysis service of Nightingale Health, Helsinki, Finland.
Keywords: Cancer diagnosis; Predictive and prognostic markers; Oncology and carcinogenesis not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi